The Royal Air Force "At Home" : The History Of RAF Air Displays From 1920. (H.B.) - Watson, Ian Smith (Pen & Sword Military, 2010)
Military public relations endeavours ultimately seek to build a sense of common interests and aims, and so generally foster good relations with the people they defend, and there in ensure a stable society. The armed forces when engaging on any public relations exercise, have traditionally sought to provide an entertaining spectacle. For years this has been typified by parades, bands, mock battles, drill displays and other relevant feats of military prowess which have captured the imagination of the public and inspired potential recruits.The 20th Century brought a new dimension to the field of warfare and subsequently added a new strand to the fabric of public ceremony and displays by the armed forces. That new dimension was the arrival of powered flight. Display flying began within five years of the Wright Brothers making their milestone first flight. The first events staged in Britain which centred on demonstrations by flying machines, were organised by the town councils of Blackpool and Doncaster and were held within days of each other in October 1909.